Taas – ticketing as a service - Ferreira, João C. (2013)
The goal of this research work is to introduce the concept of a lower cost flexible system for ticketing purposes implemented on a cloud platform. We propose therefore the evolution of the traditional architecture of ticketing for a cloud based architecture in which the core processes of ticketing are offered through a Software-as-a-Service (SaaS) business model, which can be subscribed by operators that pay-per-use. Ticketing terminal equipment (e.g. gates, validators, vending machines) are integrated in the cloud environment. This approach is achieved by moving business logic from terminals to the cloud. Each terminal is registered to be managed by each own operator, configuring a multi-tenant implementation which is vendor hardware independent, allowing to address elasticity and interoperability issues. The elasticity of the cloud will support the expansion/implosion of small (transport) operators business around electronic ticketing. In the near future, this ticketing solution will promote collaboration between transport operators.